Research on the Selection of Vaccine Seeds with the HI Method Approach to Improve the Quality of Avian Infuenza Vaccines - Nuraeni, Nining; Bustanudin, Entang; Susanti, Dine Resti; Rachmanita, Intan Nur; Wijayanti , Desri; A. Rantam, Fedik (Journal La Medihealtico, 2024)
AI virus is a virus that is easily mutated because it has a single chain of RNA that is unstable, so many strains appear in the field. Currently in the field (in Indonesia), it is known that there are 2 vaccine strains that dominate, namely AI H5N1 Clade 2.1.3 and AI H5N1 Clade 2.3.2. The incompatibility of seed viruses used as vaccine seeds will hinder the eradication of AI disease in Indonesia. Therefore, it is necessary to select and develop seed viruses as new vaccine seed candidates to obtain vaccines with high quality, safe, homologous, and able to cover viruses in the field. Development activities carried out by researchers aim to obtain vaccine seeds that are able to protect against AI clade 2.1.3 virus and AI clade 2.3.2 virus. The vaccine candidates to be developed are several vaccine candidates derived from the isolation of chicken organs from AI outbreak areas in several areas on the island of Java which include West Java, Central Java and East Java which were found around 2010 to 2013. These isolates are processed and then propagated on the SPF TAB and passaged until a high viral titter is obtained. After that, identification, pathogenicity, immunogenicity and protective tests were carried out. From the results of this development, AI C-8 and C-11 virus seeds were obtained which are able to protect against both AI Clade 2.1.3 and AI Clade 2.3.2.